The effect of linguistic detail in police interview transcripts on perceptions of an interviewee - Tompkinson, James; Haworth, Kate (Language and Law / Linguagem e Direito, 2025)
The question of what constitutes a “linguistically accurate” transcript is highly relevant for transcribers of police interview recordings. Does the inclusion of aspects of speech such as pauses, emphasis and laughter improve the quality of an interview transcript? Or does it make transcripts more difficult to interpret, and affect how interviewees are perceived? In this paper, we explored whether the provision of a more linguistically detailed transcript made perceptions of an interviewee more aligned with the corresponding audio recording. Results showed mixed effects, and differences depending on the trait being perceived and the interview content. Our work suggests that the inclusion of additional linguistic detail in transcripts does not systematically make perceptions of interviewees more aligned with audio recordings, although there may some scope for including the most salient features in transcripts. Our research illustrates the connected nature of speech perception and person perception in the context of evidential records of spoken interaction.